Association between a dietary index for gut microbiota and breast cancer history in adult women: findings from NHANES 2011–2020 - Fan, Zhiwei; Li, Liang; Bu, Lingling; Geng, Zhihui; Liu, Song (Frontiers in Nutrition, 2025)
BackgroundGut microbiota plays a crucial role in cancer development, yet limited studies have explored microbiota-oriented diets in relation to breast cancer risk. The aim was to investigate the association between a gut microbiota–oriented dietary index (DI-GM) and breast cancer risk among U.S. women.MethodsThis cross-sectional study analyzed data from 6,083 women aged ≥20 years from NHANES 2011–2020. The DI-GM score, based on intake of microbiota-beneficial and microbiota-unfavorable foods, was constructed from 24-h dietary recalls. Breast cancer history was self-reported. Multivariable logistic regression models were used to examine associations. Subgroup analyses assessed potential effect modification.ResultsHigher DI-GM scores were significantly associated with lower odds of breast cancer (adjusted OR = 0.94, 95% CI: 0.89–0.99, p = 0.012). Women with DI-GM scores ≥6 had a 33% lower likelihood of breast cancer compared to those with lower scores (adjusted OR = 0.67, 95% CI: 0.45–0.89, p = 0.006). Subgroup analyses showed consistent associations across age, ethnicity, smoking, alcohol, and BMI categories without significant interactions.ConclusionFollowing a diet that supports a healthy gut microbiota may help reduce the risk of breast cancer. Additional longitudinal and mechanistic research is needed to validate these results.